Understanding investment analysis and portfolio management - Brown, Keith C. (Philippines : Cengage Learning Asia Pte Ltd, 2012)
This text equips you with a solid understanding of investment instruments, capital markets, behavioral finance, hedge funds, international investing and much more. Real-world examples and hands-on applications bring chapter concepts to life as you learn to use the same tools as investment professionals.
Includes bibliographical references and index.
Keywords: INVESTMENT ANALYSIS